2008
DOI: 10.1016/s0140-6736(08)61159-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eradication of Helicobacter pylori on incidence of metachronous gastric carcinoma after endoscopic resection of early gastric cancer: an open-label, randomised controlled trial

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
921
4
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,119 publications
(963 citation statements)
references
References 43 publications
(38 reference statements)
22
921
4
16
Order By: Relevance
“…Ten of 14 patients were male and the mean age at the occurrence of gastric cancer after eradication was 71 (9) years. The indications for eradication therapy were endoscopic mucosal resection for early gastric cancer in 10 cases (Fukase et al 2008), gastric ulcer in 2 cases, duodenal ulcers in 1, and idiopathic thrombocytopenic purpura in 1 case (Kohda et al 2002), and the mean period from the eradication to the subsequent occurrence of gastric cancer was 74 (44) months. In 10 patients who had received endoscopic mucosal resection previously, since none of the new cancerous lesions emerged from the preceding resection scar, they were unlikely to have been residual cancer due to incomplete endoscopic procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten of 14 patients were male and the mean age at the occurrence of gastric cancer after eradication was 71 (9) years. The indications for eradication therapy were endoscopic mucosal resection for early gastric cancer in 10 cases (Fukase et al 2008), gastric ulcer in 2 cases, duodenal ulcers in 1, and idiopathic thrombocytopenic purpura in 1 case (Kohda et al 2002), and the mean period from the eradication to the subsequent occurrence of gastric cancer was 74 (44) months. In 10 patients who had received endoscopic mucosal resection previously, since none of the new cancerous lesions emerged from the preceding resection scar, they were unlikely to have been residual cancer due to incomplete endoscopic procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies consistently reported that H. pylori eradication had some inhibitory effects on the subsequent development of gastric cancer, at least in certain conditions (Take et al 2005;Takenaka et al 2007;Fukase et al 2008;Ogura et al 2008). However, it also has been revealed that there are sporadic cases of gastric cancer even after successful eradication (Kamada et al 2005;Yanaoka et al 2009;de Vries et al 2009).…”
mentioning
confidence: 99%
“…In gastric cancer in which Helicobacter pylori (H. pylori) infection-associated, aberrant methylation is shown to be implicated [10], eradication of H. pylori has been shown to reduce the risk of developing gastric cancer not only in animal studies, but also in a prospective, multicenter, randomized, controlled trial [11].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the further advanced the existing preneoplastic condition is, the less likely it is that H pylori eradication will stop gastric cancer development (37,59) , a randomized study of patients undergoing H pylori eradication following early gastric cancer resection was able to demonstrate a reduction in the appearance of metachronous gastric cancer (66) .…”
Section: Randomized Controlled Trials Conducted In Colombia Andmentioning
confidence: 99%
“…Metachronous tumors in the gastric remnant have been described in up to 10% of patients undergoing gastric, endoscopic or surgical resection for early gastric cancer (182,187,194) . A recent randomized controlled trial from Japan showed that eradication of H pylori in patients undergoing endoscopic resection for early gastric cancer, followed for 3 years, was able to reduce the risk of developing metachronous gastric cancer from 4 per 100 persons per year to 1.4 per 100 persons per year in the eradicated group (66) . Also considered high-risk patients for development of gastric cancer are those undergoing gastric resections for benign diseases (peptic ulcer, for example) and patients carrying other gastric neoplasias such as adenoma and MALT lymphoma.…”
Section: Statement 19mentioning
confidence: 99%